Behavior of Estonian Oil Shale in Acidic Oxidative Conditions - Niidu, Allan; Grénman, Henrik; Muldma, Kati; Kaldas, Kristiina; Mikli, Valdek; Lopp, Margus (Frontiers in Chemical Engineering, 2022)
Oxidation has been a long sought-after alternative to classical thermal processing of oil shale, in order to obtain valuable raw materials for the chemical industry. A number of different methods have been applied, but thus far, one of the most effective ways to transform oil shale to value added products, such as aliphatic terminal dicarboxylic acids, is oxidation with nitric acid. In order to obtain insight into the reactivity of oil shale in nitric acid, a study focusing on the kinetics and behavior of oil shale particles during oxidative leaching was performed. To that end, the particle size distribution, surface area, and carbon content were measured during the leaching process in addition to the amount of total residual solids. Determining the carbon content of the solid residue was proposed as a simple measure of the reaction progress, based on the hypothesis that all carbon measured by elemental analysis correspond to organic carbon since inorganic carbon is present as carbonate in the starting material and would have dissolved under the acidic conditions. To our surprise, the solid residue had a significant amount of organic carbon in the form of calcium oxalate mineral. Thus, measuring carbon content in the solid residue could provide only an indirect measure of the overall oxidation degree provided that the amount of oxalates was known. In general, the results revealed that the total solid residue amounts to between 20% and 34% of the initial values after 24 h of the reaction, while the total carbon content ranges from 4% to 14% of the starting values. These results show that we were able to extract around 90% of the organic carbon present in the solid phase.